2015
DOI: 10.3402/ijch.v74.28780
|View full text |Cite
|
Sign up to set email alerts
|

Whiteboard animation for knowledge mobilization: a test case from the Slave River and Delta, Canada

Abstract: ObjectiveTo present the co-creation of a whiteboard animation video, an enhanced e-storytelling technique for relaying traditional knowledge interview results as narratives.DesignWe present a design for translating interview results into a script and accompanying series of figures, followed by technical steps to create a whiteboard animation product.MethodOur project used content analysis and researcher triangulation, followed by a collaborative process to develop an animated video to disseminate research find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…Videos depicted the delta day 2016 activities and were translated into English, Cree, and Chipewyan. A “Delta Ways Remembered” video (Bradford and Bharadwaj 2015 ) used whiteboard animation to tell stories from elders and local people from the South Slave region of the NWT. 2 Maps illustrated the three inland river deltas.…”
Section: Results #2: Birth Of a Traveling Exhibit: Standardization Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Videos depicted the delta day 2016 activities and were translated into English, Cree, and Chipewyan. A “Delta Ways Remembered” video (Bradford and Bharadwaj 2015 ) used whiteboard animation to tell stories from elders and local people from the South Slave region of the NWT. 2 Maps illustrated the three inland river deltas.…”
Section: Results #2: Birth Of a Traveling Exhibit: Standardization Anmentioning
confidence: 99%
“…Art has also enhanced teaching through deeper emotive and sensory experiences (Marshall 2014 ; Jacobson et al 2016 ; Jacobson et al 2007 ) including community and participatory theater (Strickert and Bradford 2015 ; Brown et al 2017 ). Collaborative art has been used to understand diverse values against the backdrop of changing socio-cultural environments (Billings et al 2007 ; Zurba and Berkes 2014 ; Zurba and Friesen 2014 ), and to understand socio-ecological change (Bradford and Bharadwaj 2015 ; Rathwell and Armitage 2016 ). Artistic expression can connect researchers with more subjective emotions as well as multiple senses in support of intuitive “perceptions of coherence” (De Wolf and Lumer 2017 :16) that might respect different ways of knowing and enable connection to the hidden third space in transdisciplinary practice.…”
Section: Art Transdisciplinarity and Boundary Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the key ethical aspects in these models are that exploitive or polluting activities need to be held in check and that no natural hierarchy exists (i.e., humans are not above other species). YQFN Elders and others have revealed that community ethics and values based on the interconnectedness of nature are changing (Bradford and Bharadwaj ). Examining the drivers of this potential point of differentiation in these participants’ perspectives from those of the TEK models is a future goal.…”
Section: Resultsmentioning
confidence: 99%
“…These videos depict a hand drawing images on a whiteboard, accompanied by narration, sound effects and music. This format can be tailored to specific populations and used to share information, including research results (Bradford and Bharadwaj 2015).…”
Section: Introductionmentioning
confidence: 99%